Улс төрийн философи сэтгэлгээний үечлэл - Д.Болд-Эрдэнэ (Politology, 2023)
Political philosophy is the historic phenomenon. Philosophers explain that political philosophy mentality has many different opinion. Leo Strauss’s category of classic and modern political philosophy tend to recognize in nowadays. In this article have been put out many ideas about period of political philosophy mentality.